Emergent Self‐Assembly Pathways to Multidimensional Hierarchical Assemblies using a Hetero‐Seeding Approach. Issue 59 (26th September 2019) - Liu, Yin; Gong, Yanjun; Guo, Yongxian; Xiong, Wei; Zhang, Yifan; Zhao, Jincai; Che, Yanke; Manners, Ian
Abstract: The controlled formation of complex and functional 1‐, 2‐, and 3D hierarchical assemblies from molecular building blocks represents a key current challenge. Herein, we report the use of a seeded growth approach for a series of perylenediimide‐based molecules (PDIs 1 –4 ) to access otherwise inaccessible self‐assembly pathways that yield complex hierarchical structures. The key to the new approach is to use hetero‐seeds which possess a different composition and morphology from that of the molecular building block. For example, a nanotube seed (from PDI 3 ) and a microribbon seed (from PDI 4 ) were found to initiate different self‐assembly pathways for PDI 1, which normally assembles to yield nanocoils. This led to the formation of unprecedented 3D scroll‐like and scarf‐like hierarchical nanostructures, respectively. Also, the hetero‐seeds from PDI 3 initiate hidden self‐assembly pathways of PDI 2 to generate 1D tubular heterojunctions. Significantly, this new strategy offers new opportunities to create emergent and functional hierarchical and complex structures from small molecule precursors. Abstract : The use of a hetero‐seeded growth approach for a series of perylenediimide‐based molecules (PDIs 1 –4 ) to access otherwise inaccessible self‐assembly pathways that yield complex hierarchical structures. A nanotube seed (from PDI 3 ) and a microribbon seed (from PDI 4 ) were found to initiate different self‐assembly pathways for PDI 1, which normally assembles to yield nanocoils. This led to the formation of unprecedented 3D scroll‐like and scarf‐like hierarchical nanostructures, respectively. Also, the hetero‐seeds from PDI 3 initiate hidden self‐assembly pathways of PDI 2 to generate 1D tubular heterojunctions.